Improving multidisciplinary communication at ward board rounds using video enhanced reflective practice. Issue 1 (11th February 2015) - Hellier, Cyril; Tully, Vicki; Forrest, Sandra; Jaggard, Pamela; MacRae, Morag; Habicht, Dirk; Greene, Alexandra; Collins, Karen
Abstract: The priority to ensure patient safety and use resources effectively, demands attention and innovation. Video enhanced reflective practice (VERP) provides training based upon analysis of film clips of one's professional practice to develop practical insight into the processes of communication, so that effective changes can be made to ongoing behaviour and practice. In this case the focus was on multi-disciplinary communication within daily board rounds on an acute medicine and care of the elderly ward. Baseline assessment and post intervention testing of perceptions of change by both full and core team were undertaken to establish the impact of VERP training. In addition pre and post focus group discussion and film analysis supplemented evaluation. The findings support the view that after VERP training of a core team, board rounds were seen as consistently easier to participate in, providing improved focus, were more efficient in goal setting and resulting in better care for patients as well as improved pathways to discharge. This suggests benefits to the communication "culture" of a multidisciplinary team resulting in increased benefits for the wider team. It is concluded that the use of tailored VERP training for personal, professional and team development is relevant, feasible, and worthy of further testing and investigation.